Correlation of Biometric Parameters With Endothelial Distance in EVO ICL Phakic Lens Implantation - Beltrán-Murcia J.; Álvarez-Rementería Capelo L.; Blázquez-Sánchez V. (Journal of Ophthalmology)
Conclusions: The correlations between GAP and pre- and postoperative variables highlight its relationship with anterior segment anatomy after EVO ICL implantation. However, as a postoperative measurement, GAP does not determine the correct positioning of the lens.